Empirical therapy of bloodstream infections caused by extended-spectrum β-lactamase-producing Enterobacteriaceae - Tang, C Q; Li, J Q; Xia, Z F; Wang, H; Lü, K Y; Xiao, S C; Deng, A M; Huang, Y (Zhong hua yi xue za zhi, 2016)
To compare the clinical outcomes and costs associated with carbapenems and β-lactam/β-lactamase inhibitor combinations (BLBLIs) for the empirical treatment of patients with extended-spectrum β-lactamase (ESBL)-positive Enterobacteriaceae bloodstream infections (BSIs). The medical records of individuals diagnosed with ESBL-producing Escherichia coli and Klebsiella pneumoniae BSIs between January 2014 and June 2015 at Changhai Hospital were reviewed. Patients were divided into two groups based on the empirical therapy (carbapenems group and BLBLIs group). Propensity score matching in a 1∶1 ratio was used to match the patients from two groups. Clinical outcomes and costs were compared before and after matching. One hundred and fifty-eight patients were analyzed, 93 in the carbapenems group and 65 in the BLBLIs group. Before matching, the two groups were significantly different in department distribution, tumor rate, deep vein catheter rate, urinary catheter rate, nasogastric tube rate, and mechanical ventilation